Formation Pathways of Compact Elliptical Galaxies: Perspective of Internal Structures - Jinwon Yi; Soo-Chang Rey; Suk Kim; Youngdae Lee (The Astrophysical Journal)
We present a structural analysis of 138 compact elliptical galaxies (cEs) in the redshift range of z < 0.05 using the Sloan Digital Sky Survey (SDSS) DR12 data. We perform single- and double-component Sérsic model fitting to their SDSS r -band surface brightness profiles. By dividing cEs into those with [cE(w)] and without [cE(w/o)] a bright host galaxy, we find a significant structural dichotomy: the majority (∼85%) of cE(w)s exhibit single-component profiles, while a similar proportion (∼85%) of isolated cE(w/o)s display double-component profiles, characterized by a compact, inner component and a diffuse, disk-like outer component. These results suggest that host-associated cE(w)s primarily form through the tidal stripping of larger progenitors, resulting in a compact bulge-like core. In contrast, isolated cE(w/o)s appear to form intrinsically at early epochs, likely through gas-rich mergers, and retain disk-like outer structures. The Sérsic index distribution of cE(w)s with single-component structure indicates progenitor types ranging from pseudobulge to classical bulge, supported by differences in stellar populations. A small fraction of cEs, including double-component cE(w)s and single-component cE(w/o)s, suggests complex evolutionary channels involving environmental capture or ejection. Our results emphasize that the structural characteristics of cEs, specifically the presence or absence of an extended outer envelope, serve as a crucial diagnostic tool to distinguish tidally stripped remnants from intrinsically formed low-mass cEs in isolation.